Development of an E2 ELISA Methodology to Assess Chikungunya Seroprevalence in Patients from an Endemic Region of Mexico - Young Chan Kim; César López-Camacho; Nallely Garcia-Larragoiti; Alan Cano-Mendez; Karina Guadalupe Hernandez-Flores; Carlos Alonso Domínguez-Alemán; Maria Antonieta Mar; Héctor Vivanco-Cid; Martha Eva Viveros-Sandoval; Arturo Reyes-Sandoval (Viruses, 2019)
Chikungunya fever is a debilitating disease caused by Chikungunya virus (CHIKV) that can result in long-lasting arthralgias. The early diagnosis of CHIKV relies on PCR during the acute infection phase to allow differential diagnosis with other co-circulating arboviruses such as dengue and Zika. Alternatively, serology can support diagnosis and provide epidemiological information on current and past outbreaks. Many commercial serological ELISA assays are based on the inactivated whole CHIKV, but their sensitivity and specificity show great variability. We produced recombinant CHIKV E2 that is suitable for ELISA assays, which was used for the serodiagnosis of CHIKV infections occurring in an arbovirus endemic Mexican region within Michoacán state. A cross-sectional study was conducted in 2016−2017; sera was obtained from 15 healthy donors and 68 patients presenting undifferentiated febrile illness. Serum samples were screened by RT-PCR and by our in-house ELISA assay. Our results indicate that IgM and IgG anti-CHIKV E2 antibodies were detected with our ELISA assay with higher sensitivity than a commercially available CHIKV ELISA kit. Our simple and sensitive ELISA assay for the serodiagnosis of CHIKV infections can be applied to population-based seroprevalence surveys and has potential for monitoring vaccine immunogenicity in CHIKV vaccine clinical trials.